Evolution of dealloying induced strain in nanoporous gold crystals. Issue 17 (20th April 2017) - Chen-Wiegart, Yu-chen Karen; Harder, Ross; Dunand, David C.; McNulty, Ian
Abstract : We studied the evolution of dealloying-induced strain along the {111} in a Ag–Au nano-crystal in situ, during formation of nanoporous gold at the initial stage of dealloying using Bragg coherent X-ray diffractive imaging. Abstract : We studied the evolution of dealloying-induced strain along the {111} in a Ag–Au nano-crystal in situ, during formation of nanoporous gold at the initial stage of dealloying using Bragg coherent X-ray diffractive imaging. The strain magnitude with maximum probability in the crystal doubled in 10 s of dealloying. Although formation of nano-pores just began at the surface, the greatest strain is located 60–80 nm deep within the crystal. Dealloying induced a compressive strain in this region, indicating volume shrinkage occurred during pore formation. The crystal interior showed a small tensile strain, which can be explained by tensile stresses induced by the non-dealloyed region upon the dealloyed region during volume reduction. A surface strain relaxation developed, attributed to atomic rearrangement during dealloying. This clearer understanding of the role of strain in the initial stages of formation of nanoporous gold by dealloying can be exploited for development of new sensors, battery electrodes, and materials for catalysis.